Experimental and Theoretical Behavior of Reinforced Concrete Two Way Slabs Strengthened by Steel Fiber Ferrocement Layers at Tension Zone (Journal of University of Babylon for Engineering Sciences, 2018)
An experimental and analytical  behavior of strengthened reinforced  concrete two way slabs  by steel fiber ferrocement layers ,this  study  included  testing 14  simply supported two way slabs, which include 1 control slab, 13 strengthened slabs. In the strengthened slabs the effect of  the ferrocement layers with; steel fiber content in the ferrocement mortar  of (0.25,0.5,0.75.1.1.25%), thickness of ferrocement layers, the compressive strength for ferrocement mortar and wire mesh layers number of ferrocement was investigated. The mid span deflection at ultimate load and cracks pattern  were discussed.  All the reinforced concrete slab specimens were designed of the same dimensions and reinforced identically to fail in flexure. Simply supported conditions for all slabs has bean tested under central concentrated load. The experimental results show that; the ultimate loads and mid span deflection of strengthened reinforced  concrete slabs were more effected by  using the steel fiber on the ferrocement mortar, increasing the thickness of ferrocement and the compressive strength of ferrocement. Three-dimensional nonlinear finite element analysis has been used to conduct the analytical investigation, ANSYS (Version 16.0) computer program was used in this study. The analytical result from modeling in ANSYS program exhibited a good agreement with experimental results.